Development of A PLC-Based Automated Test System for The Life Cycle Evaluation of The Caster Wheel Brake Mechanisms in Medical Devices - Kene, Harsh Dilip; Patil, Sudhir Madhav; Guru, Prasenjit; Bachhav, Piyush Dipak (International Journal of Basic and Applied Sciences, 2025)
Caster wheels used in medical devices such as ultrasound systems are critical for mobility and safety. Their brake mechanisms must maintain performance over repeated use. This study aims to develop and implement a Programmable Logic Controller (PLC)-based automated ‎test system to evaluate the life cycle performance of caster wheel brake mechanisms under accelerated testing conditions. A dedicated ‎mechatronics test setup was designed incorporating a pneumatic actuator, proximity sensor, and strain gauge for real-time monitoring and ‎control. A fixture was developed to simulate repeated brake engagement and disengagement cycles using a single pneumatic cylinder. The ‎PLC controlled the test sequence and recorded sensor feedback, while manual force measurements were taken at specific intervals up to the ‎designated cycles corresponding to the life cycles of the braking mechanism, CL. The caster wheel brake engagement and disengagement forces ‎were measured across eleven distinct test instances: 0, 0.1CL, 0.2CL, and so on up to CL. These tests were conducted over ten intervals. The ‎measured forces showed consistent results, with variations limited to within ±2% of the required rated values for both engagement and disengagement. This indicated minimal wear or loss in functionality over CL. The system operated reliably for CL continuous cycles, validating ‎the mechanical robustness of both the test rig and the caster wheel components. This automated system offers a time-efficient solution for ‎reliability testing of the braking mechanism of the caster wheel. However, the present study focuses on the caster wheel used in the medical equipment manufacturing sector. It enables consistent testing without human intervention, ensuring better quality assurance and predictive ‎maintenance insights. The developed PLC-based test system provides a reliable platform for life cycle evaluation of caster wheel brake ‎mechanisms. Its modular design and automation capability make it adaptable for testing various wheel types and supporting further research ‎in reliability engineering‎.